El simbolismo moderno del "Diario de un poeta recién casado", Juan Ramón Jiménez - Lacalle Ciordia, María Ángeles (Huarte de San Juan. Filología y Didáctica de la Lengua, 1999)
In our essay we have studied five symbols: the child, the boat, the spring, the rose and the evening, through which Juan Ramón Jiménez offers the poetic vision of “Diario”. At the same time we have picked out the basic notions of modern symbolism in his poetic work.